Investigation of the association between HLA-G polymorphisms and obesity - Mohammad, Alaa; Mıhçıoğlu, Deniz; Gerçeker, Filiz; Aksoy, Başar (Journal of Surgery and Medicine, 2022)
Background/Aim: Obesity is a global public health problem seen worldwide, with an increasing prevalence over time. Obesity is a multifactorial disease affected by both genetic and environmental factors. It is accompanied by many other diseases, the most important of which are immune system disorders. Induction of suppression of HLA-G molecule T and B lymphocytes is associated with natural killer cells and antigen-presenting cells. The HLA-G gene shows functional polymorphisms in regulatory regions. The HLA-G gene is slightly more conserved compared to other HLA genes, both in the same population and among different populations. The aim of this research is to determine the association of HLA-G gene polymorphisms (14 bp insertion/deletion 3 'UTR (rs66554220), rs41557518, and rs1063320) with obesity. Methods: Fifty normal (BMI ≤30) individuals having no obesity-related chronic disorder, and 50 obese (BMI≥ 30) individuals were included in the study. After DNA isolation, PCR and PCR-RFLP methods were used for genotyping. Results: The genotype frequencies of HLA-G polymorphisms (rs66554220, rs41557518, and rs1063320) in the normal and obese groups were compared, and as a result, no significant difference was found (P>0.05). Conclusion: No significant association was found between rs66554220, rs41557518, and rs1063320 polymorphisms and obesity.